2012
DOI: 10.1111/j.1469-1795.2012.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Applying the tools of ecological immunology to conservation: a test case in the Galapagos sea lion

Abstract: Infectious disease threatens biodiversity and human health on a global scale, and disease emergence may become more common as humans further encroach on habitats and modify environments. To accurately assess the risk of disease emergence in free‐ranging populations of vertebrates, we require an understanding of the dynamics of immunity in the wild. We applied techniques from the emergent discipline of ecological immunology to describe immune activity and dynamics in the endangered Galapagos sea lion Zalophus w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 102 publications
(111 reference statements)
1
43
0
Order By: Relevance
“…These strategies include management to reduce the contact of humans and domestic dogs with sea lions, health studies in rookeries exposed and not exposed to human disturbances [52,53], the establishment of annual population monitoring in the entire archipelago, and the standardization of count methods. However, strategies for improving the quality of the marine and terrestrial habitats of sea lions have not been fully implemented.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…These strategies include management to reduce the contact of humans and domestic dogs with sea lions, health studies in rookeries exposed and not exposed to human disturbances [52,53], the establishment of annual population monitoring in the entire archipelago, and the standardization of count methods. However, strategies for improving the quality of the marine and terrestrial habitats of sea lions have not been fully implemented.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Understanding variation in disease susceptibility in non-model systems has become a growing priority (Pedersen and Babayan, 2011), particularly in systems where infectious disease represents a conservation threat. For instance, a recent study of cellular and humoral immune activity in endangered Zalophus wollebaeki (Galapagos sea lions) from two colonies revealed that animals in a human-impacted colony suffered greater immune-stimulatory pressure, which could increase the likelihood of disease emergence (Brock et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously measured variation in 12 immune-related physiological measures during the first two years of life in the Galapagos sea lion [38], and discussed its significance in the conceptual framework of ecological immunology [8][10]. We found that Galapagos sea lions from the human-impacted colony on San Cristobal had relatively higher levels of immune activity – quantified using cell-mediated and humoral immune components, and snapshot and cumulative measures – than sea lions from a colony on the uninhabited island of Santa Fe [38]. In this study we used three of the previously described immune measures: total immunoglobulin G (IgG) concentration, the in vivo inflammation response to phytohemagglutinin (PHA), and total leukocyte concentration.…”
Section: Methodsmentioning
confidence: 99%
“…In this study we used three of the previously described immune measures: total immunoglobulin G (IgG) concentration, the in vivo inflammation response to phytohemagglutinin (PHA), and total leukocyte concentration. To aid the interpretation of this immune variation we took repeated measurements of known individuals from two age classes [38]: pups (3 months or younger) and juveniles (6 months or older). In pups, in which the involution of the thymus is unlikely to have taken place [39], increases in IgG and total leukocyte concentrations are likely to be driven by the establishment of protective baseline levels in response to the post-natal antigenic environment [40].…”
Section: Methodsmentioning
confidence: 99%